The game : inside the secret world of major league baseball's power brokers - Pessah, Jon (New York, NY : Little, Brown and Company, 2015)
The founding editor of ESPN the Magazine and Pulitzer Prize nominee presents the extraordinary inside story of baseball's last 20 years, during which the genius and struggle for power of three men saved the game from self-destruction.
In the fall of 1992, America's National Pastime is in crisis and already on the path to the unthinkable: canceling a World Series for the first time in history. The owners are at war, their decades-long battle with the players has turned America against both sides, and the players' growing addiction to steroids will threaten the game's very foundation. It is a crucial moment in the game's history that catalyzes a struggle for power by three strong-willed men: Commissioner Bud Selig, Yankees owner George Steinbrenner, and union leader Don Fehr. It's their uneasy alliance at the end of decades of struggle that pulls the game back from the brink and turns it into a money-making powerhouse that enriches them all. This is the real story of baseball, played out against a tableau of stunning athletic feats, high-stakes public battles, and backroom political deals-- with a supporting cast that includes Barry Bonds and Mark McGwire, Joe Torre and Derek Jeter, George Bush and George Mitchell, and many more. Drawing from hundreds of extensive, exclusive interviews, this is a rigorously reported, definitive account of how an enormous struggle for power turned disaster into baseball's Golden Age.--From publisher description.
Changing of the guard (1992-1994). In Bud we trust ; A whole new world ; Inextricably linked ; Resurrection ; System failure ; For the good of the game ; Everything to lose ; Fehr strikes -- Art of the deal (1994-1996). Endgame ; Fehr's day in court ; Back to work ; New foundations ; True lies ; Dynasty ; Deal! -- Secret of success (1997-2000). Setting up shop ; Almost perfect ; Secrets ; Question of balance ; Ring for Roger ; Hope and faith ; Dollars and no sense -- Power play (2001--2003). Miller time ; More than a game ; Bud's bluff ; Trouble ahead ; New deals ; Renovations ; Tipping point ; Looking for answers ; Testing positive -- Revisionist history (2004-2007). Government intervention ; Curses ; Selig's choice ; Transfer of power ; Calling Mr. Mitchell ; Last stand ; A change in plans ; Mitchell gets his man ; Questions and answers -- Legacy (2008-2010). The more things change ; Moving on ; Road to Cooperstown.
Includes bibliographical references (pages [597]-630) and index.
Keywords: Baseball -- History; Major League Baseball (Organization) -- History; Baseball -- History